2010
DOI: 10.1038/emboj.2010.333
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation and phosphorylation of SRSF2 control cell fate decision in response to cisplatin

Abstract: SRSF2 is a serine/arginine-rich protein belonging to the family of SR proteins that are crucial regulators of constitutive and alternative pre-mRNA splicing. Although it is well known that phosphorylation inside RS domain controls activity of SR proteins, other post-translational modifications regulating SRSF2 functions have not been described to date. In this study, we provide the first evidence that the acetyltransferase Tip60 acetylates SRSF2 on its lysine 52 residue inside the RNA recognition motif, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
172
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(184 citation statements)
references
References 50 publications
(79 reference statements)
6
172
1
4
Order By: Relevance
“…These results suggest that PTM by lysine acetylation could be involved in the regulation of pre-mRNA processing events. In agreement, Edmond and collaborators have recently found that the SR protein SRSF2 is modified by acetylation within its RNA binding domain at K52 (39). SRSF2 acetylation levels are regulated by the opposing action of the acetyl-transferase TIP60 and the deacetylase HDAC6 such that acetylation by TIP60 reduces SRSF2 protein levels through proteasome-dependent degradation, while deacetylation by HDAC6 exerts the opposite effect.…”
Section: Post-translational Modifications Of Sr Proteins: Above and Bmentioning
confidence: 59%
“…These results suggest that PTM by lysine acetylation could be involved in the regulation of pre-mRNA processing events. In agreement, Edmond and collaborators have recently found that the SR protein SRSF2 is modified by acetylation within its RNA binding domain at K52 (39). SRSF2 acetylation levels are regulated by the opposing action of the acetyl-transferase TIP60 and the deacetylase HDAC6 such that acetylation by TIP60 reduces SRSF2 protein levels through proteasome-dependent degradation, while deacetylation by HDAC6 exerts the opposite effect.…”
Section: Post-translational Modifications Of Sr Proteins: Above and Bmentioning
confidence: 59%
“…52 In the context of genotoxic stress, cisplatin treatment decreases TIP60-dependent acetylation and increases SRPK2-dependent phosphorylation of SRSF2 (also called SC35). 22 Interestingly, many targets of ATM/ATR, protein kinases playing key roles in DNA damage signaling, are RNA-binding proteins including SFs. 53 Also interesting, the protein kinase AKT that promotes cell survival increases the anti-apoptotic caspase 9b isoform through phosphorylation of SRSF1 (also called ASF/SF2).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…For example, SRSF2 mediates the regulation of AS events in multiple apoptosis-related genes, including caspase 8, caspase 9, Bcl-x and c-flip. 20,22 Likewise, SRSF1 controls multiple apoptosis-related AS, including those of Bcl-x, Mcl1 and caspase 9. 44 It will be interesting to identify the whole sets of AS events controlled by stress-induced modifications of these and other SFs, and to determine how different modifications of the same factor (e.g., SRSF2 regulation at the levels of transcription, AS, and protein localization, phosphorylation and acetylation in response to cisplatin) might impact on different sets of exons and/or other levels of gene expression where this factor is involved.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…12 As such, SRSF2 mutation is thought to pre-dispose early progenitor cells to malignant selection, perhaps via its role in the acetylation/phosphorylation network and as an important regulator of DNA stability and mRNA splicing. 13 We have now sequenced for SRSF2 mutation in our cohort of mastocytosis patients, previously characterized for both KIT and TET2 mutations, 7 and have revealed a striking association between SRSF2 mutation and advanced disease types.…”
Section: Introductionmentioning
confidence: 99%